Characteristics of α−acetolactate synthase and diacetyl production by Enterococcus faecium ETw7 and Enterococcus faecalis ETw23 - Vallejo, Marisol (2008)
Diacetyl is an essential flavor compound in fermented dairy products such as cheese. In this work kinetic and biochemical characteristics of α−acetolactate sinthase (α-ALS) and its influence on the formation of diacetyl were studied in Enterococcus faecium ETw7 and Enteroccoccus faecalis ETw23. In both cases, the kinetic parameters revealed a low affinity for piruvate, as has been described in other lactic acid bacteria. E. faecium ETw7 displayed its maximal enzimatic activity at pH 5.8-6.2 and 40 ºC, however under cheese ripening condition (pH 5.0 and 15 oC) the remaining activity was low. α−ALS from E. faecalis ETw23 showed its maximal activity at ripening pH, the optimun temperature was determined at 40 ºC and the remaining activity at 15 ºC was about 30% of its maximal one. The growth and diacetyl formation by both strains were studied in De Man-Rogosa-Sharpe medium (MRS) and MRS supplemented with citrate (MRScit). In both medium the growth rate of E. faecium ETw7 was comparable but an enhancement in biomass was observed in MRScit. In the case of E. faecalis ETw23 a higher growth rate, between 6 h and 10 h, and a higher biomass were achieved in MRScit. After 24 h of growth, E. faecium ETw7 reached a level of 20.4 μM of diacetyl in MRS and 26.1 μM in MRScit, while E. faecalis ETw23 achieved levels of 41.8 μM and 61.7 μM, respectively. The results of the study suggest that E. faecalis ETw23 may contribute to flavor development in cheese through its role in diacetyl production.